Phase II study of celecoxib with docetaxel chemoradiotherapy followed by consolidation chemotherapy docetaxel plus cisplatin with maintenance celecoxib in inoperable stage III nonsmall cell lung cancer. Issue 1 (25th August 2017) - Takhar, Harminder; Singhal, Nimit; Mislang, Anna; Kumar, Raj; Kim, Laurence; Selva‐Nayagam, Sid; Pittman, Ken; Karapetis, Chris; Borg, Martin; Olver, Ian N.; Brown, Michael P.
Abstract: Title: Phase II study of celecoxib with docetaxel chemoradiotherapy (CRT) followed by consolidation chemotherapy docetaxel plus cisplatin with maintenance celecoxib in inoperable stage III nonsmall cell lung cancer. Introduction: Concurrent CRT has been associated with improvement in absolute 5‐year survival by 10% and is the standard of care for inoperable stage III nonsmall cell lung cancer. Preclinical evidence suggests that cyclooxygenase‐2 inhibition may increase the efficacy of CRT. Methods: Patients were treated with CRT (weekly docetaxel at 30 mg/m 2 over 6 weeks with concurrent external beam radiotherapy with 60 Gy in 30 fractions) followed by consolidation chemotherapy with docetaxel and cisplatin, each at 75 mg/m 2 given 3 weekly for four cycles. Patients were to receive celecoxib 400 mg twice daily during treatment. Prophylactic cranial irradiation (30 Gy in 15 fractions) was offered if there was disease response. Results: Twenty‐four patients commenced CRT. Nineteen patients commenced consolidation therapy with 14 patients completing treatment. Twelve patients had treatment with celecoxib. In the total cohort, the median overall survival (mOS) was 21 months and progression‐free survival (PFS) was 16 months. Overall response rate was 59% and disease control rate was 82%. Three patient deaths occurred. Significant grade 3/4 toxicity included radiation pneumonitis (17%), febrile neutropenia (17%), infection/sepsis with or with neutropenia (25%) and esophagitis (12.5%). Retrospective analysis of celecoxib versus no celecoxib treatment showed favorable mOS 26.5 versus 17.5 months and PFS 22 versus 16 months, but this did not reach statistical significance. Conclusions: The activity of this regimen has been demonstrated. Treatment‐related toxicity was substantial. The role of celecoxib in addition to CRT could not be demonstrated in this study because of the small number of patients.